2018
DOI: 10.3201/eid2401.171240
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Feline Influenza A(H7N2) Virus

Abstract: During December 2016–February 2017, influenza A viruses of the H7N2 subtype infected ≈500 cats in animal shelters in New York, NY, USA, indicating virus transmission among cats. A veterinarian who treated the animals also became infected with feline influenza A(H7N2) virus and experienced respiratory symptoms. To understand the pathogenicity and transmissibility of these feline H7N2 viruses in mammals, we characterized them in vitro and in vivo. Feline H7N2 subtype viruses replicated in the respiratory organs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 23 publications
0
34
0
2
Order By: Relevance
“…Expanded surveillance in mammalian hosts has yielded several surprises, including divergent IAVs in bats (H17 and H18) [26], a new genus of Orthomyxovirus (influenza D) in bovines [27], and the establishment of IAV in canines (CIV) during the 2000s: CIV-H3N8 in the US [28] and CIV-H3N2 in Asia [29]. An outbreak of H7N2 in felines in New York [30] suggests that other mammalian species could potentially be capable hosts for IAV transmission at certain thresholds of animal density and movement. However, IAVs have relatively low reproductive numbers (R), just above the threshold of 1 required for transmission, and require high contact rates between susceptible hosts to maintain transmission.…”
Section: Iav Evolution Never Follows Predictions: What Will the Next mentioning
confidence: 99%
“…Expanded surveillance in mammalian hosts has yielded several surprises, including divergent IAVs in bats (H17 and H18) [26], a new genus of Orthomyxovirus (influenza D) in bovines [27], and the establishment of IAV in canines (CIV) during the 2000s: CIV-H3N8 in the US [28] and CIV-H3N2 in Asia [29]. An outbreak of H7N2 in felines in New York [30] suggests that other mammalian species could potentially be capable hosts for IAV transmission at certain thresholds of animal density and movement. However, IAVs have relatively low reproductive numbers (R), just above the threshold of 1 required for transmission, and require high contact rates between susceptible hosts to maintain transmission.…”
Section: Iav Evolution Never Follows Predictions: What Will the Next mentioning
confidence: 99%
“…The authors suggested that low‐level spread of virus between cohoused ferrets occurs in the absence of productive infection. Hatta et al assessed transmission of the A/feline/NY/2016 in ferrets and cats. In contrast to Belser et al 1 of 3 pairs of ferrets placed in direct contact showed productive infection and seroconversion but no respiratory droplet transmission to ferrets placed in adjacent cages.…”
Section: Discussionmentioning
confidence: 99%
“…Despite low pathogenicity in ferrets, the A(H7N2) viral outbreak quickly spread to most of the cats in the quarantine facility. Hatta et al showed that A/feline/NY/2016 can, although inefficiently, transmit among cats via contact and respiratory droplet transmission. The high rate of transmission of A/feline/NY//2016 may, in part, reflect the large number of animals in the facility and the lack of central ventilation and/or dedicated exhaust systems to mitigate the high potential for continued suspension and reaerosolization of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…A LPAIV of the H7N2 subtype, which circulated in live poultry markets in the eastern and northeastern US during 1994-2006, was identified as the causative source of an outbreak in a cat shelter in New York City in December 2016, subsequently spreading to multiple shelters in the states of New York and Pennsylvania. Infected cats experienced clinical signs of coughing, sneezing, and runny nose from which they fully recovered (17). Under experimental conditions, feline H7N2 subtype was found to replicate efficiently in cat upper and lower respiratory tracts and had the ability to transmit among cats, FIGURE 1 | Dogs and cats as mixing vessels for influenza A virus.…”
Section: Epidemiology Of Iav In Cats and Dogsmentioning
confidence: 99%